Towards Reform in Subject-Matter Preparation of Science Teachers: Collaboration Between a Faculty of Science and a Faculty of Education - McNay, Margaret (Canadian Journal of Higher Education, 1993)
Recent research in the subject-matter preparation of science teachers reveals serious shortcomings in undergraduate programs, particularly their failure to provide students with adequate conceptual understandings, their perpetuation of myths and stereotypes about science and scientists, and their tendency to turn students (particularly women) away from science. In an attempt to alleviate these problems, and to stem declining enrollment in science programs at both secondary and post-secondary levels, the Faculty of Education and the Faculty of Science at the University of Western Ontario are collaborating in the development of a new Honours B.Sc. program. The proposal is for an interdisciplinary program permitting a broader selection of courses and a more comprehensive introduction to science than is offered in current Honours B.Sc. programs. The new program is not intended exclusively or even primarily for prospective teachers but for all students. A proposal for action research and program evaluation is also described.